Ballooning behavior in the golden orbweb spider Nephila pilipes (Araneae: Nephilidae) - Lee, Vanessa M. J.; Kuntner, Matjaž; Li, Daiqin (Frontiers in Ecology and Evolution, 2015)
Ballooning, a mode of aerial dispersal in spiders, is an innate behavior that requires appropriate physiological and meteorological conditions. Although only rarely reported in the golden orbweb spiders, family Nephilidae, the large geographic distributions of most nephilids—in particular of Nephila species—would imply that these spiders likely routinely disperse by ballooning in spite of giant female sizes. Here we study ballooning behavior in the golden orbweb spider Nephila pilipes (Fabricius, 1793). Specifically, we test for the propensity of spiderlings to deploy ballooning as a dispersal mechanism. We subjected a total of 59 first-instar spiderlings to a wind experiment at two wind speeds (2.17 ± 0.02 m s-1 and 3.17 ± 0.02 m s-1) under laboratory conditions. Under an average wind speed of 3.17 m s-1, none of the spiderlings exhibited pre-ballooning or ballooning behavior. However, at an average wind speed of 2.17 m s-1, 53 (89.8%) spiderlings showed pre-ballooning behavior, and 17 (32.1%) of the pre-ballooners ultimately ballooned. Our results concur with prior reports on spiderlings of other families that pre-ballooning behavior is a requirement for ballooning to occur. Furthermore, although we cannot rule out other dispersal mechanisms such as synanthropic spread, our findings suggest that the widespread N. pilipes uses ballooning to colonize remote oceanic islands.